Mek1 and Mek2 Functional Redundancy in Erythropoiesis - Beuret, Laurent; Fortier-Beaulieu, Simon-Pierre; Rondeau, Vincent; Roy, Sophie; Houde, Nicolas; Balabanian, Karl; Espéli, Marion; Charron, Jean (Frontiers in Cell and Developmental Biology, 2021)
Several studies have established the crucial role of the ERK/MAPK pathway in hematopoietic cell proliferation and differentiation. MEK1 and MEK2 phosphorylate and activate ERK1 and ERK2. However, whether MEK1 and MEK2 differentially regulate these processes is unknown. To define the function of Mek genes in the activation of the ERK pathway during hematopoiesis, we generated a mutant mouse line carrying a hematopoietic-specific deletion of the Mek1 gene function in a Mek2 null background. Inactivation of both Mek1 and Mek2 genes resulted in death shortly after birth with a severe anemia revealing the essential role of the ERK pathway in erythropoiesis. Mek1 and Mek2 functional ablation also affected lymphopoiesis and myelopoiesis. In contrast, mice that retained one functional Mek1 (1Mek1) or Mek2 (1Mek2) allele in hematopoietic cells were viable and fertile. 1Mek1 and 1Mek2 mutants showed mild signs of anemia and splenomegaly, but the half-live of their red blood cells and the response to erythropoietic stress were not altered suggesting a certain level of Mek redundancy for sustaining functional erythropoiesis. However, subtle differences in multipotent progenitor distribution in the bone marrow were observed in 1Mek1 mice suggesting that the two Mek genes might differentially regulate early hematopoiesis.